A dementia communication training intervention based on the VERA framework for pre-registration nurses: Part I developing and testing an implementation strategy. (April 2018) - Naughton, Corina; Beard, Chloe; Tzouvara, Vasiliki; Pegram, Anne; Verity, Rebecca; Eley, Rhiannon; Hingley, David
Abstract: Background: People living with dementia experience progressive difficulty in expressing physical and emotional needs. Health care staff including student nurses require training to develop compensatory communication strategies. However, there is no standardised foundation level dementia communication training within pre-registration curricula. Aim: This article describes the theoretical underpinnings and development of a foundation level dementia communication skills training based on the VERA (Validation, Emotion, Reassurance, Activity) framework. Method: The training strategies drew on behavioural change theory using the COM-B model and Gagné's 9 Events of Instruction. The VERA framework was operationalised using a multicomponent teaching strategy. The intervention was refined based on quality improvement Plan-Do-Study-Act cycles with feedback from people living with dementia, facilitators and student nurses. Data collection used semi-structured questionnaires ( n  = 51) and four focus group ( n  = 19) interviews with students. Data analysis involved descriptive statistics and thematic analysis. Results: The intervention was a 2.5-hour face-to-face training session delivered at the start of students' older adult unit placement with follow-up reflection sessions during placement. Training was delivered to 51 students, all students described the training as useful and would recommend it to their peers. Elements of the training that were highly valued were: opportunities to express concerns in caring for people with dementia, applying the VERA framework using role play and outlining realistic expectations of VERA. Students recognised the need for on-going training especially for more complex patients. Conclusion: Combining behaviour change and education theory with stakeholder feedback strengthened the development of VERA as a foundation level dementia communication training for pre-registration nurses.